Examine The Effect of Word-of-Mouth and Electronic Word-of-Mouth on Consumers' Perceived Risk in Taiwan: A Case Study on Online Shopping - Lin, Hung-Miao (2011)
Online shopping has become one of the most popular activities on the Internet in recent years. Due to the emergence of electronic commerce and the wide spread of the Internet, there is a new shopping channel for consumers to purchase products or services they need, that is, online shopping. In the past, researchers found that consumers had different online purchase behavior in terms of their demographics. However, the results of this thesis show that as time goes by, consumers become more familiar with the Internet and online shopping, the difference of consumers online purchase behavior due to different demographics has become smaller. In this thesis, no significant differences were found when examining consumers' online purchase behavior by using demographic information such as gender, age, education level, occupation, and monthly income. Another focus of this thesis is to examine whether word of mouth and electronic word of mouth have the ability to reduce consumers' perceived risk toward online shopping and to further increase their purchase intention. The analyzed results show that not only traditional word of mouth, but also electronic word of mouth can reinforce consumers' perception of online shopping, reduce their perceived product risk and perceived finance risk toward online shopping, as well as increase consumers' shopping intention of purchasing from the Interent.